Agreement of diagnosis between admission and emergency department and the final diagnosis on discharge from the psychiatric ward, tertiary hospital, Malaysia - Mohamad Ismail, Maung Ko @ Hajee; Akter, Seikh Farid Uddin; Htwe, Ohnmar; Musa, Ramli; Abu Bakar, Ahmad Zafri; Ko, Ba Min (Japan International Cultural Exchange Foundation (JICEF), 2013)
Introduction: Psychiatric emergency is a clinical condition where prompt psychiatric attention with psychotherapeutic intervention is necessary to facilitate a recovery and prevent permanent harm. Modern Psychiatric Emergency Service is now applying highly complex and comprehensive set of interventions and treatment models in psychiatric centers. Many patients discharged from chronic hospital into the community had relapse of symptoms. The only access to the mental health care of these patients and the patients from under privileged class was through Emergency Departments or Psychiatric Emergency Service. The Emergency Department was over loaded with mental health cases and it is a national crisis in the United States now. Psychiatric emergency assessment is expected to detect acute presenting symptoms of mental illness, psychiatric symptoms of underlying medical conditions and dangerous behaviors to self or others. Accurate diagnosis is crucial for rapid implementation of appropriate initial treatment. Objective: The Objective of our study is to assess the agreement of diagnosis in Emergency Department and Final Discharge diagnoses from the Ward. The reliability of the diagnosis was investigated from the comparison of the diagnoses in Emergency and Final Discharge diagnoses. Methods: It is a retrospective record review study. Medical officers from Psychiatric Ward collected data in data collection form. All first admission cases of 2006 and 2007 were taken. Data analysis was done applying kappa and chi-square statistics excluding chance concordance and over diagnosis. Results: The result of our study did not compare favorably with that of previous studies. Conclusion: The excellent agreement originated from application of uniform criteria, structured interview, descriptive psychopathology, acquiring significant information for diagnoses. Reliable psychiatric diagnoses are possible in the skilled hands. © 2013 Japan International Cultural Exchange Foundation & Japan Health Sciences University.